2021
DOI: 10.37363/bnr.2021.2355
|View full text |Cite
|
Sign up to set email alerts
|

Tamarillo Juice (Solanum betaceum Cav) as An Alternative to Increase Hemoglobin Levels for Pregnant Women with Anemia

Abstract: Introduction: World Health Organizations recommends pregnant women to consume 120-240 mg of iron (in the form of Ferrum) per day and increase the dose by 400 mg 3 times a day if the Anemia is severe. One of the herbal therapies that can increase hemoglobin levels is Tamarillo (Solanum Betacum Cav) with a vitamin C level of 25 mg, Fe 2,765 ppm. The research objective was to analyze the effect of Tamarillo juice consumption in increasing hemoglobin (HB) levels of pregnant women with Anemia. Methods: Quasi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Most of the tukang suun who involved in this study were over 45 years old and most of them were no longer of reproductive age, so that the anemia experienced was not severe. Where in theory, women of reproductive age are more prone to experience more severe anemia because they are still experiencing the menstrual cycle and allow them to breastfeed and give birth [13].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the tukang suun who involved in this study were over 45 years old and most of them were no longer of reproductive age, so that the anemia experienced was not severe. Where in theory, women of reproductive age are more prone to experience more severe anemia because they are still experiencing the menstrual cycle and allow them to breastfeed and give birth [13].…”
Section: Discussionmentioning
confidence: 99%
“…Anemia in pregnancy is defined as a condition when the hemoglobin level in the blood is less than 11 g/dl. The result of the study (Simbolon and Sitompul, 2021) showed that on average 1 of 2 pregnant women whose hemoglobin levels were measured had anemia (96 responden examined pregnant wome) and 41 respondent (43%) had anemia. The effects of anemia on the fetus include low birth weight, lack of oxygen in the womb, and spontaneous and regular breathing failure.…”
Section: Introductionmentioning
confidence: 96%
“…Development is an increase in the function of the body's organs that can be achieved through learning. The development consists of moving or gross and fine motor skills, hearing, seeing, communicating, speaking, emotional-social, independence, intelligence, and moral development (Juana Linda Simbolon, 2021). Child development is closely related to the children's nutritional status.…”
Section: Introductionmentioning
confidence: 99%